Die Bestimmung des arterio-portalen Durchblutungsverhältnisses der Leber- Ergebnisse mit 99mTc-Hepatobida und Methoden-Übersicht - Carl, I.; Müller-Schauenburg, W. (Nuklearmedizin - NuclearMedicine, 1990)
The arterial-to-portalvenous blood flow ratio (APV) has been determined routinely within liver bile studies carried out with 99mTc-hepatobida. Out of 1300 patients studied since 1978, 80 were analysed in detail concerning the fixed time parameters to separate the arterial and the portalvenous phase. The arterial phase was assumed to end 4 s after the first aortal peak, immediately followed by a portalvenous phase of 12 s duration. The “triangular area approach” of Biersack (1977) and George (1974) developed for pertechnetate and colloid, was directly applied to hepatobida. The fixed phase limits of hepatic circulation described above were compared to circulation parameters obtained from the beginning of the right ventricular recirculation and from the first decline of the spleen curve (for the end of the arterial phase), and from the second left ventricular peak (for the end of the portal phase). Our 4 s of aortal to end-arterial time agreed excellently with a corresponding control value of 4.1 s, as did the duration of the portal phase with 12 s compared to a control value of 12.1 s. An upper normal value of 45% APV was established, based upon sensitivity, specificity and a classification of hepatic curves. The “triangular area approach” appears at first to be inconsistent from a methodological point of view. We present a critical typology of assessing the APV. Basically we distinguish between strictly intravasal and all other types of tracer. The former are studied adequately by deconvolution and subsequent “real” area approaches, reflecting the full tracer passage through the liver. All not strictly intravasal tracers (pertechnetate, colloid, hepatobida) are subjected to a model assumption of a pure uptake without relevant tracer elimination during the first pass. We conclude that the Biersack-George method may be regarded as a heuristic correction of an amplitude approach within our typology, and that our fixed phase limits are justified by circulation analysis.